The Main Directions of Development of the Higher Education Management System in The Republic of Kazakhstan - TUREKULOVA, Dametken; LESBAYEVA, Gulnara; YESTURLIEVA, Aigul; SAIMAGAMBETOVA, Gauhar; AUBAKIROVA, Zhanna; KOZLOVA, Natalya (Journal of Advanced Research in Law and Economics, 2017)
The main trends in the sphere of education of the Republic of Kazakhstan are represented in the scientific paper. An analysis of the management system of higher education in Kazakhstan has been conducted. Modern trends in the sphere of education of the republic and the tasks facing its various levels call for a rethinking of their role, functions and place in the general education system, and the development of new approaches in their further development. A highly effective education system is one of the main factors ensuring sustainable growth of the country's economy and Kazakhstan society. The goal of the ongoing reforms in the education system of our state is to ensure its qualitative transformation in the conditions of a market economy taking into account globalization.